Microbiome of a Reef-Building Coral Displays Signs of Acclimation to a Stressful Shallow Hydrothermal Vent Habitat - Reigel, Alicia M.; Paz-García, David A.; Hellberg, Michael E. (Frontiers in Marine Science, 2021)
Most tropical reef corals live at temperatures near 27C and pH values near 8. Conditions outside of these can stress corals and lead to bleaching, disease and death. However, some corals can survive in marginal or extreme habitats outside of these ranges. To date there is a paucity of knowledge about the role that associated microbes may play in the acclimation of corals to extreme habitats. Here we explore differences in the compositional and functional profile of the microbiomes of the scleractinian coral Porites panamensis living both on and off stressful shallow-water hydrothermal vents. The environment near the vents is extreme, with temperatures exceeding 80C and pH values below 6. Coral microbiomes under stress often exhibit increased diversity, increased abundance of pathogenic bacteria, and functional profiles that shift towards pathways associated with pathogenic taxa. Samples from along a transect that crossed an arc of hydrothermal vents were sequenced for the 16S rRNA gene (V4 region). On-vent coral microbiomes were distinct from those of off-vent corals, but did not have increased alpha or beta diversity. On-vent samples had a higher relative abundance of the beneficial endosymbiont, Endozoicomonas. On- and off-vent microbiomes did not differ in overall abundance of the endolithic green alga Ostreobium, however, a single ASV, identified as O. quekettii was more abundant in on-vent corals. Ostreobium can provide many of the same benefits to corals as zooxanthellae and their symbiosis is better maintained under thermal stress. Surprisingly, on-vent coral microbiomes had relatively fewer microbial taxa that are known to be pathogenic or are associated with stress, than off-vent corals. The predicted functional profiles of on-vent microbiomes revealed enrichment of pathways related to aerobic respiration, fermentation and amino acid biosynthesis, but not of virulence-related pathways. Our results suggest that P. panamensis microbiomes have acclimated to the extreme environment of the hydrothermal vent habitat rather than showing signs of stress. These results exemplify the need to focus efforts on examining the mechanisms of resilience, including symbioses with microbiota, in corals living in extreme environments in an effort to design better management strategies for reef-building corals on thermal and pH stress.